Dark-bright optical solitons conversion via an optical add/drop filter - Mitatha, S.; Chaiyasoonthorn, N.; Yupapin, P. P. (My University, 2009)
We propose a new system of the dark-bright solitons conversion using a micro and nano ring resonators incorporating an optical add/drop filter, where the add/drop filter can be used to convert the dark soliton to bright soliton. The key advantage of the system is that the detection of the dark soliton pulse is normally difficult due to the low level of the input power. Firstly, a dark soliton pulse is input into a micro ring resonator then propagating into a smaller micro and nano ring resonators, respectively. Secondly, the add/drop filter is applied (connected) into the ring system, where the bright and dark solitons are obtained via the drop and through (or throughput) ports of the add/drop filter, respectively. Results obtained have shown that the detected soliton power can be controlled by the input soliton power and the ring resonator coupling coefficient, which is enough to use in the transmission link. © 2009 Wiley Periodicals, Inc. Microwave Opt Technol Lett 51: 2104-2107, 2009 Published online in Wiley InterScience (www.interscience.wiley.com).
Keywords: Add/drop filter; Dark soliton; Nanowaveguide; Solitons conversion